Publication among academic staff and students: an analysis from the ethical perspective - Urrutia Soto, María Teresa (Investigación y Educación en Enfermería, 2015)
This article analyzes, from the ethical perspective, the authorship of particles carried out among students and professors and their potential conflicts. After the literature review, it has been found that the Vancouver criteria that should be fulfilled for the attribution of authorship of an article are not popularly known by students and academic staff. Many problems are posed in this area, among which the following are highlighted: ghost writer, honorary author, and incorrect assignment in the order authors should appear. The professor-student relationship brings with it implicit risks that could lead to conflict, against which it is the academician who should be cautious to curtail any ethical fault when assigning the authors. The measures recommended to avoid conflicts of authorship among students and academic staff are: early assignment of the authors, reflection among academicians, education to students/academic staff, and external control conducted by journal editors. Conclusion is that lack of awareness of the criteria of authorship by academicians and students is the principal problem in the attribution of authorships. It is indispensable to improve this knowledge and look after the application of said criteria in practice. How to cite this article: Urrutia MT. Publication among Academic Staff and Students: an Analysis from the Ethical Perspective. Invest Educ Enferm. 2015; 33(3):